Reiki: uma abordagem do ponto de vista das emoções - Ferreira, Renata Shirley da Silva (2018)
Reiki has as integral therapeutic approach, taking into account the physical, mental, emotional and spiritual dimensions, as important components that contribute to the disease and health condition of the individual, as part of the Integrative and Complementary Practices in Health (PICS). His systematizer, Mikao Usui believed that when the soul was at peace - and by soul one understands emotions and thoughts, whose term is kokoro in Japanese - the body healed itself. Since emotions are an important factor in the process of illness and health of the individual, Reiki was investigated from this point of view. This dissertation aimed at analyzing the perceptions of users treated with Reiki therapy, within their emotional contexts, under the perspective of phenomenology: what do they experience during and after the consultations? How did they experience it? Understanding Reiki within the context of the subjectivity of these people, describe their sensations. Therefore this dissertation had a qualitative bias, involving bibliographical review and field research. Within the bibliographic review, Reiki was investigated within its historical contexts (Eastern and Western), as well as a therapeutic practice inserted in the PICS and its relationship with emotions: how emotional can contribute to the state of illness and health of the individual and how Reiki can act in this condition. In the field research, through interviews, the perceptions of people attended with Reiki, with their emotional demands, were collected, which sought the Center for Integrative and Complementary Practices in Health - Equilibrium of Being, establishing a dialogue between literature and of the participants. After the interviews were collected during the field research, a phenomenological investigation was carried out, seeking to identify what was in common among the reported perceptions. It was concluded that the people involved reported feelings of well-being, physical perceptions, visualizations and extracorporeal perceptions and the reflection of their own state of illness within the emotional context. The categories found in field research were found in the literature. However, it has been noticed that there is almost no room for the expressions of people who experience Reiki, which shows the specificity of this research in letting users, within their contexts of life express themselves, without worrying about making any judgment about the truth of these experiences, since the methodological resource allows: phenomenology.